Productive and reproductive performances of indigenous chicken in the rural condition of Bangladesh - Jahan, S; Islam, F; Bhuiyan, MSA; Bhuiyan, AKFH (Bangladesh Journal of Animal Science, 2017)
The study was aimed at investigating the productive and reproductive performances of the rural chicken in Bangladesh. A total of 200 indigenous chickens in the villages of Sherpur district in Bangladesh was used in this study to collect the data on body weight at hatch (BWH), body weight at sexual maturity (BWS), body weight gain up to sexual maturity (BSBG), body weight gain from sexual maturity to one year of age (BYSG), body weight at one year of age (BWY), age at sexual maturity (AGSX), eggs per clutch (EGC), clutches per year (CLY), hatchability (HATCH) and survivability (SURV). The data showed that cap headed (CH) chickens were good meat producer (1027.14±25.32g meat at one year of age), and Non-Descript Deshi (ND) chickens were good egg producer with 12.03±0.11 eggs per clutch and 4.15±0.07 clutches per year, respectively. The effects of village, sex and type of birds on AGSX of indigenous chickens were significant but, only the effects of chicken type on EGC were significant (P<0.01). At present study, most of growth and reproductive traits found positively correlated and this might be suggestive that selection for one trait would affect the other positively. These results could be used as a guideline for planning, conservation and improvement of indigenous chickens of Bangladesh. Bang. J. Anim. Sci. 2017. 46 (2): 121-127